Aerosolized hyaluronic acid and its applications - Raia, V.; Sepe, A.; Tosco, A.; De Gregorio, F.; Amato, F. (Acta Biomedica Atenei Parmensis, 2014)
Although the interaction of low MW HA fragments with surface receptors such as TLRs may explain how HA can favor the inflammatory response, some physical and chemical properties, such as high MW HA, may increase its capability to retain water and to preserve the distensibility of elastic fibers that is dependent on the interaction with water molecules, thus enhancing pulmonary ventilation. Encouraging clinical results provide the beneficial effect of inhaled HA in CF patients who have previously shown poor tolerance to aerosolized hypertonic saline solution.